Pengaruh Return On Equity Dan Earning Per Share terhadap Harga Saham pada PT. Bank Mandiri (Persero), Tbk Periode 2010-2019 - Tanwir Tanwir; Waluyo Jati (Prodi Akuntansi STIE Hidayatullah Depok, 2021)
This study aims to determine the effect of Return On Equity and Earning Per Share on Stock Prices at PT. Bank Mandiri (Persero), Tbk. The method used is explanatory research. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study, Return on Equity has a significant effect on stock prices by 41.5%, hypothesis testing is obtained t count> t table or (2.381> 2.306). Earning per share has a significant effect on stock prices by 47.6%, hypothesis testing is obtained t count> t table or (2.697> 2.306). Return On Equity and Earning Per Share simultaneously have a significant effect on stock prices, the regression equation Y = -7,040 + 0.440X1 + 0.013X2 and a determination value of 72.9%, hypothesis testing obtained the value of F count> F table or (9,423> 4,350 ).